Detection of the natural distribution of Entomopathogenic Nematodes in cultivated fields in Al-Hasakah Governorate, Syria - Darwish, Ali; Al-Assas, Khaled; Haidar, Asmaa; Ishaq, Elias; El Mohamed, Ismail (Arab Journal for Sciences and Research Publishing, 2016)
The aim of the study was to investigate the natural distribution of insect pathogenic nematodes in fields cultivated with various crops from the areas of Amouda, Qamishli and Darbasiya in Al Hasakah Governorate. Several field trips were conducted from the end of March to the end of April 2014-2015, And a depth of 10-30 cm within the Rhizosphere, excluding the surface layer of the soil, at a rate of 4 simple samples from each Zaczak field, from which a single compound sample (2 kg) was taken.     The results of the study showed the absence of insect pathogenic nematodes in the soil of the samples taken from the cultivated fields in Al-Hassakeh Governorate. The results of the analysis of the soil samples showed that these soils are muddy. Type of soils It is difficult to find insect pathogenic nematodes. The pH in the studied soils ranges between 7.12-7.8 pH.
Keywords: investigation; entomopathogenic nematodes; cultivated fields; Hasaka; Syria